PENGARUH KEKERINGAN TERHADAP PERTUMBUHAN DAN PERKEMBANGAN TANAMAN NYAMPLUNG (Callophylum inophyllum L.) DAN JOHAR (Cassia florida Vahl.) DARI PROVENAN YANG BERBEDA - Nur Hidayati; Rina Laksmi Hendrati; Arie Triani; Sudjino Sudjino (Jurnal Pemuliaan Tanaman Hutan, 2017)
Nyamplung (Callophylum inophyllum L.) and johar (Cassia florida Vahl.) are alternative plants that are resistant to drought. Global warming that occurred in the last few years caused extreme climate change, one of which is drought. The purpose of this research were to examine and determine the growth and development of plants and the response of morphology, physiology, and anatomy of these plants to drought condition, and adaptive species to drought. This research used drought stress treatment for 10 days, 20 days, 30 days, and 40 days, while control plants were watered every 2 days. Each treatment used 3 replications. Parameters observed were plant height, stem diameter, number of leaves, leaf area, proline levels, plant water content, total dry weight, root dry weight, stomata index, root anatomy, anatomy of stem, and leaf anatomy. Physiological data obtained were analyzed using T-test. The results showed that plants responded to drought stress by decreasing plant height, stem diameter, number of leaves, leaf area, root dry weight, total dry weight, water content of plants, transpiration rate, stomata lindex, root cortex thickness, leaf mesophyll thickness, leaf phloem thickness, other wise occurred increasing level of proline, root epidermis thickness, stem xylem diameter, stem cortical thickness and leaf xylem thickness. Johar plant was more adaptive plant to drought stress than nyamplung plant.